Introduction to wireless systems - Shankar, P. M. (John Wiley & Sons, Inc., 2002)
This unique text is the first and only introduction to wireless systems written specifically for undergraduate students.. The text helps you learn the science and engineering of mobile and wireless communication by clearly developing analytical tools, fundamental physics, and communication theory. Coverage spans the complete range of topics related to modern wireless communications, including propagation effects, wireless modems, cells and cell design, diversity, dispersion, fading, multiplexing techniques, 3G systems, OFDM systems, Bluetooth wireless networks, and more.